The Right to Inclusive Education of Persons with Disabilities in Italy. Reflections and Perspectives - Sara Carnovali (Athens Institute for Education and Research, 2017)
The paper aims to examine in detail the level of implementation of the right to inclusive education of persons with disabilities stipulated in the Italian legal system, with a particular focus on the Constitution and on the principles stated by the Italian Constitutional Court's case law. The right to education of persons with disabilities is protected through different instruments, constitutional requirements and principles, legislation and case law, and at different territorial levels, representing an emblematic example of integrated or multi-level protection of fundamental rights. However, in reality people with disabilities still face many challenges in accessing education, and this article critically discusses the reform currently planned by the Government designed to address these problems